Fabrication and characterization of regenerated silk scaffolds reinforced with natural silk fibers for bone tissue engineering1. Issue 8 (21st February 2013) - Mobini, Sahba; Hoyer, Birgit; Solati‐Hashjin, Mehran; Lode, Anja; Nosoudi, Nasim; Samadikuchaksaraei, Ali; Gelinsky, Michael
Abstract: We introduce a novel Bombyx mori silk‐based composite material developed for bone tissue engineering. Three‐dimensional scaffolds were fabricated by embedding of natural degummed silk fibers in a matrix of regenerated fibroin, followed by freeze‐drying. Different ratios of fibers to fibroin were investigated with respect to their influence on mechanical and biological properties. For all scaffold types, an interconnected porous structure suitable for cell penetration was proven by scanning electron microscopy. Compressive tests, carried out in static and cyclic mode under dry as well as wet conditions, revealed a strong impact of fiber reinforcement on compressive modulus and compressive stress. Cell culture experiments with human mesenchymal stem cells demonstrated that the fiber/fibroin composite scaffolds support cell attachment, proliferation, as well as differentiation along the osteoblastic lineage. Considering the excellent mechanical and biological properties, novel fiber/fibroin scaffolds appear to be an interesting structure for prospect studies in bone tissue engineering. © 2013 Wiley Periodicals, Inc. J Biomed Mater Res Part A:, 2013.